Do household finances constrain unconventional fiscal policy? - Scott Baker; Lorenz Küng; Leslie McGranahan; Brian T. Melzer (Federal Reserve Bank of Chicago, 2018)
When the zero lower bound on nominal interest rate binds, monetary policy makers may lack traditional tools to stimulate aggregate demand. We investigate whether "unconventional" fiscal policy, in the form of pre-announced consumption tax changes, has the potential to meaningfully shift durables purchases intertemporally and how it is affected by consumer credit. In particular, we test whether car sales react in anticipation of future sales tax changes, leveraging 57 pre-announced changes in state sales tax rates from 1999-2017. We find evidence for substantial tax elasticities, with car sales rising by over 8% in the month before a 1% increase in the sales tax rate. Responses are heterogeneous across households and sensitive to supply of credit. Consumers with high credit risk scores are most able to pull purchases forward. At the same time, other effects such as customer composition and attention lead to an even larger tax elasticity during recessions, despite these credit frictions. We discuss policy implications and the likely magnitudes of tax changes necessary for any substantive long-term responses.
Keywords: D12; E21; G01; G11; H31; 330; counter-cyclical fiscal policy; credit market frictions; consumer durables